DAMPAK ATAS OVERKAPASITAS PADA LAPAS TANGERANG DALAM PEMENUHAN HAK NARAPIDANA MENURUT UNDANGUNDANG NOMOR 12 TAHUN 1995 (STUDI PADA LEMBAGA PEMASYARAKATAN PEMUDA KELAS II A TANGERANG) - Devi Ulan Dari; Ade Adhari (Fakultas Hukum Universitas Tarumanagara, 2021)
Correctional Institutions as representatives of the government have tried to provide coaching services to prisoners as well as possible. In the context of this guidance, efforts are also made to ensure the fulfillment of the rights of prisoners. This study aims to determine the inhibiting factors of prisoners' rights and their impact at the Class II A Tangerang Youth Correctional Institution on the rights of prisoners in the Class II A Tangerang Youth Correctional Institution. This research is empirical research, where field interviews are conducted with the Youth Prison Class II A Tangerang, then the study of library materials by studying, reading, analyzing and analyzing the literature is also carried out to develop studies related to the title of this research.From the study it can be concluded that the impact of overcapacity in the Class II A Tangerang Children's Prison causes a lack of supervision of inmates, thus interfering with the rights of prisoners. Prisons whose number of prisoners exceed the existing capacity will hamper the functions and goals of the correctional institution and have the potential not to achieve the goals of development within the correctional institution. Various preventions have also been carried out by building new prisons and sending prisoners to prisons that are not classified as overcapacity